Maturity-onset Diabetes of the Young (MODY) in Pregnancy: A Review - Majewska, Agata; Stanirowski, Paweł; Wielgoś, Mirosław; Bomba-Opoń, Dorota (Current Diabetes Reviews, 2023)
Hyperglycaemia in pregnancy is one of the most common complications of pregnancy and is generally diagnosed as gestational diabetes mellitus (GDM). Nevertheless, clinical symptoms of hyperglycaemia in pregnancy in some cases do not match the clinical manifestations of GDM. It is suspected that 1-2 % of women diagnosed with GDM are misdiagnosed maturity-onset diabetes of the young (MODY). MODY often has a subclinical course; thus, it is challenging for clinicians to aptly diagnose monogenic diabetes in pregnancy. Proper diagnosis is crucial for the effective treatment of hyperglycaemia in pregnancy. Many studies revealed that misdiagnosis of MODY increases the rate of complications for both mother and fetus. This literature review reports the current knowledge regarding diagnosis, treatment, and complications of the most common types of MODY in pregnancy.
Keywords: HNF1A-MODY